Climate warming alters subsoil but not topsoil carbon dynamics in alpine grassland. (6th October 2019) - Jia, Juan; Cao, Zhenjiao; Liu, Chengzhu; Zhang, Zhenhua; Lin, Li; Wang, Yiyun; Haghipour, Negar; Wacker, Lukas; Bao, Hongyan; Dittmar, Thorston; Simpson, Myrna J.; Yang, Huan; et al.
Abstract: Subsoil contains more than half of soil organic carbon (SOC) globally and is conventionally assumed to be relatively unresponsive to warming compared to the topsoil. Here, we show substantial changes in carbon allocation and dynamics of the subsoil but not topsoil in the Qinghai‐Tibetan alpine grasslands over 5 years of warming. Specifically, warming enhanced the accumulation of newly synthesized ( 14 C‐enriched) carbon in the subsoil slow‐cycling pool (silt‐clay fraction) but promoted the decomposition of plant‐derived lignin in the fast‐cycling pool (macroaggregates). These changes mirrored an accumulation of lipids and sugars at the expense of lignin in the warmed bulk subsoil, likely associated with shortened soil freezing period and a deepening root system. As warming is accompanied by deepening roots in a wide range of ecosystems, root‐driven accrual of slow‐cycling pool may represent an important and overlooked mechanism for a potential long‐term carbon sink at depth. Moreover, given the contrasting sensitivity of SOC dynamics at varied depths, warming studies focusing only on surface soils may vastly misrepresent shifts in ecosystem carbon storage under climate change. Abstract : Warming, accompanied by enhanced growth of deep‐rooted grasses, is shown to cause substantial changes in subsoil carbon dynamics of a Qinghai‐Tibetan grassland. Subsoils under warming show new carbon accumulation in the silt‐clay fraction, increased concentrations of sugars and lipids as well as enhanced degradation of lignin likely due to labile‐carbon‐stimulated cometabolism. The above shifts stand in contrast to the unaltered belowground net primary productivity and soil carbon dynamics in the topsoil, underscoring the high sensitivity of deep soil carbon cycling to warming in the alpine grassland.